Soybean: Evaluation of Inoculation - I. A. Ciampitti; Eric Adee; J. Kimball; G. I. Carmona (Kansas Agricultural Experiment Station Research Reports, 2016)
A soybean crop can obtain up to 50 to 75% of its nitrogen (N) requirements from the air when the biological fixation is effectively established (Pedersen, 2007). The overall objective of this project was to quantify the response to inoculation for soybean in a field without previous history of this crop. Following this rationale, a field study was conducted during the 2015 growing season at Ottawa (east central Kansas). The treatments consisted in five different N management approaches: non-inoculated, inoculated × 1, inoculated × 2, inoculated × 3 and non-inoculated but fertilized with 300 lb N per acre as the main N source. The study was planted in an area without soybean history, the grain yield ranged from 26 to 29 bushels per acre. Greater yields were recorded when a double inoculation rate was applied (× 2), while lowest yield was related to the non-inoculated scenario. However, statistically, treatments did not present any significant yield difference. In summary, further research will be performed to be more conclusive as related to the best management approach for N in soybeans when first planted in fields without previous history of this crop.
Keywords: inoculation; soybean; nitrogen; N fertilizer; yields